Design and synthesis of redox and oxidative dual responsive block copolymer micelles for intracellular drug delivery. (December 2016) - He, Changyu; Yang, Qinglai; Tan, Lianjiang; Liu, Bingya; Zhu, Zhenggang; Gong, Bing; Shen, Yu-Mei; Shao, Zhifeng
Graphical abstract: Highlights: Copolymer PEG-SS-DMTK-PLA with both double disulfide and DMTK was synthesized. The micelles are responsive with both glutathione and reactive oxygen species. The dual responsive micelles led to much faster drug release in several cancer cells. Abstract: The need for smart materials in the area of biotechnology has accelerated the development of stimuli-responsive copolymer micelles. Here, we reported a novel dual-stimuli-responsive block copolymerPEG-DMTK-SS-PLA with both dimethyl thioketal (DMTK) and disulfide linkage incorporated into the backbone, capable of triggering fast drug release properties upon both oxidative (H2 O2 ) and reductive (GSH) environment. The CMC values of these copolymer micelles ranging from 0.051 to 0.087 mg mL −1, the average diameters are from 34 nm to 55 nm and 65 nm to 198 nm for blank and DOX-loaded micelles respectively. MTT assay conducted in NIH 3T3 cells showed the low cytotoxicity of these micelles even when the concentration reached up to 500 μg/mL. Considering tumor microenvironment's diverse in kinds of tumor cells, fluorescence microscopy, flow cytometry and MTT activity analysis were conducted in several cancer cells (e.g., cervix, lung, gastric, and colon cancer cells), and further confirmed that the dual responsivePEG-DMTK-SS-PLA micelles were degraded much faster than that of non-responsivePEG-PLA and single responsivePEG-SS-PLA andPEG-DMTK-PLA micelles. These results indicate that the dual-responsive micelles are promising for efficient anticancer drug delivery.